(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study looks at how women’s roles in India’s visual arts have changed over time, from early pioneers to modern viewpoints. It examines the particular difficulties experienced by Indian women artists in light of gender bias, cultural conventions, and societal expectations. The study emphasizes the historical contributions of prominent Indian women artists and their influence on the development of the cultural environment through an examination of case studies and artwork. an art scene, such as the rise of female art movements and collectives, the impact of feminism on artistic expression, and changes in perceptions of female artists. The article also discusses the difficulties and achievements faced by female artists in the present day, as well as current viewpoints on how women are portrayed in Indian galleries, museums, and exhibitions. Additionally, it talks on advocacy and empowerment efforts unique to India, like educational projects, mentorship programs, and grassroots movements that support diversity and inclusivity in the Indian art scene. In its conclusion, the study offers recommendations for future directions in the Indian setting, including potential trends in the representation of women in the fine arts, areas that need further research, and strategies for raising knowledge and admiration of female artists. All things considered, this study highlights the importance of building a more inclusive and egalitarian cultural community while acknowledging and honoring the contributions made by women to India’s fine arts.